2021
DOI: 10.21873/anticanres.15312
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Usage Reduced Overall Survival by over 70% in Non-small Cell Lung Cancer Patients on Anti-PD-1 Immunotherapy

Abstract: Background/Aim: There is an increasing use of immunotherapy for non-small cell lung cancer (NSCLC) patients. The present study analysed the effect of antibiotic use on the outcome of NSCLC patients undergoing treatment with anti-programmed cell death-1 (anti-PD-1) immunotherapy. Patients and Methods: This was a retrospective study of 69 NSCLC patients. Eighteen out of 69 patients received antibiotics within 21 days before or within 21 days after start of anti-PD-1 therapy. Results: Patients treated with anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Through database retrieval, 81 relevant literatures were obtained, including 8 Chinese literatures, 73 English literatures, 23 conference papers and abstracts, and 67 duplicated literatures, case reports, reviews and irrelevant contents were excluded. 37 literatures were screened strictly in accordance with the above screening process, and finally 12 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) studies were included in the quantitative analysis. A total of 6010 cancer patients were involved, of whom 1414 were treated with ABX in the treatment window of ICIs, as shown in Figure 1.…”
Section: Search Results and Patient Characteristicsmentioning
confidence: 99%
“…Through database retrieval, 81 relevant literatures were obtained, including 8 Chinese literatures, 73 English literatures, 23 conference papers and abstracts, and 67 duplicated literatures, case reports, reviews and irrelevant contents were excluded. 37 literatures were screened strictly in accordance with the above screening process, and finally 12 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) studies were included in the quantitative analysis. A total of 6010 cancer patients were involved, of whom 1414 were treated with ABX in the treatment window of ICIs, as shown in Figure 1.…”
Section: Search Results and Patient Characteristicsmentioning
confidence: 99%
“…Also, the analysis of T cells and B cells implied that these bacteria in the lung may change the immune cell infiltration in LC tissues. Recently, a retrospective study of 69 NSCLC reported that patients treated with anti-PD-1 antibodies receiving antibiotics had greatly decreased objective response rate, OS, and PFS compared to those who did not use antibiotics [ 18 ]. This result highlights that inappropriate usage of antibiotics may influence the flora of the tumor environment and impair the treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…We compared NSCLC patients receiving anti-PD-1 antibody treatment with and without antibiotics and found that both the PFS and overall survival (OS) were significantly lower in the group that used some antibiotics within 3 weeks before and after the start of anti-PD-1 antibody treatment than those in the group that did not use antibiotics. In other words, antibiotic use hampers the efficacy of ICIs [ 70 ]. Using antibiotics is known to cause dysbiosis of the gut microbiota [ 71 ], suggesting that dysbiosis could reduce the efficacy of PD-1 antibody therapy.…”
Section: Attenuation Of Ici Efficacy Via the Effects Of Antibiotics O...mentioning
confidence: 99%